THE INFLUENCE OF PRODUCT QUALITY, PRICE AND TRUST ON THE DECISION TO PURCHASE ORGANIC VEGETABLES WITH BRAND IMAGE AS AN INTERVENING VARIABLE IN THE BRASTAGI SUPERMARKET, MEDAN CITY - Cut Dian Izabella; Yusniar Lubis; Syaifuddin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
In the context of marketing organic vegetables at the Brastagi Supermarket, Medan City, this research aims to examine the influence of product quality, price and consumer trust on brand image, as well as its impact on purchasing decisions. The research method used is a quantitative approach using multiple linear regression analysis. Data was collected through the use of questionnaires distributed to supermarket consumers. The analysis results show that product quality and price have a positive effect on brand image, while trust is not statistically significant. In addition, product quality, price, and trust also have an influence on purchasing decisions, although some of them are not statistically significant. Brand image management is proven to be important in the marketing strategy of organic vegetables in supermarkets. This research provides insight into the factors that influence consumer purchasing behavior and recommends further research to expand the population coverage and research methods used.